Age Estimation by Modified Demirjian's Method in a Hospital-Based Population: A Radiographic Study - Yogesh Chhaparwal; Mathangi Kumar; Medhini Madi; Shubha Chhaparwal; Kalyana Chakravarthy Pentapati (Association of Support to Oral Health Research (APESB), 2021)
Objective: To test the modified Demirjian's method of dental age estimation on the South Indian population and correlate it with the patient's chronological age. Material and Methods: This retrospective radiographic study was performed on digital panoramic radiographs taken during a one-year duration. Radiographs of patients in the age range from 8 to 18 years were included in the study. The radiographs were examined and according to the stage of the crown and root status of the left side mandibular teeth. The stage of calcification was observed for eight teeth in the mandibular arch and was recorded in a specially designed proforma. Each rated tooth with stage was converted into a score using a conversion table specified for girls and boys. Results: 224 digital panoramic radiographs were retrieved from the radiologic database. Out of total study sample, 49.5% (n=111) were boys and 50.5% (n=113). The mean chronological and estimated dental age using dental maturity scores resulted in an overestimation of 3 years and eight months. Also, it was noted that there was a strong positive association between chronological (real) and dental age. Conclusion: It was observed that there was a strong correlation between chronological and dental age. A new formula for determining the chronological age from the estimated dental age was derived. Further studies on a larger population may prove the reliability of this age estimation method.